Modeling the effect of a prosthetic limb on 4-km pursuit performance - Childers, W. L.; Gallagher, T. P.; Duncan, J. C.; Taylor, D. K. (International Journal of Sports Physiology and Performance, 2015)
The individual pursuit is a 4-km cycling time trial performed on a velodrome. Parathletes with transtibial amputation (TTA) have lost physiological systems, but this may be offset by the reduced aerodynamic drag of the prosthesis. This research was performed to understand the effect of a unilateral TTA on Olympic 4-km pursuit performance. A forward-integration model of pursuit performance explored the interplay between power loss and aerodynamic gains in parathletes with TTA. The model is calibrated to a 4-km pursuit time of 4:10.5 (baseline), then adjusted to account for a TTA. Conditions simulated were based on typical pedal asymmetry in TTA (AMP), if foot stiffness were decreased (FLEX), if pedaling asymmetries were minimized (ASYM), if the prosthesis were aerodynamically optimized (AERO), if the prosthesis had a cosmetic cover (CC), and if all variables were optimized (OPT). A random Monte Carlo analysis was performed to understand model precision. Four-kilometer pursuit performances predicted by the model were 4:10.5, 4:20.4, 4:27.7, 4:09.2, 4:19.4, 4:27.9, and 4:08.2 for the baseline, AMP, FLEX, ASYM, AERO, CC, and OPT models, respectively. Model precision was ±3.7 s. While the modeled time decreased for ASYM and OPT modeled conditions, the time reduction fell within model precision and therefore was not significant. Practical application of these results suggests that parathletes with a TTA could improve performance by minimizing pedaling asymmetry and/or optimizing aerodynamic design, but, at best, they will have performance similar to that of intact cyclists. In conclusion, parathletes with TTA do not have a net advantage in the individual pursuit.